Identitas Budaya pada Pemain Game Online ”Sky Children of the Light”: Pendekatan Etnografi Virtual - Narasrey Merinda; Zainal Abidin; Maulana Rifai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Online Game: Sky Children of The Light is an adventure game that allows each player to meet others with different cultural backgrounds and languages without the need to enter a specific server. This game is developed by the company ThatGameCompany. The objective of this research is to understand how